Factors influencing the fee setting for orthodontic appliance placement in dental practices in the Medan Petisah Sub-district - Desta, Maorina; Lim, Davin; Pratama, Rizky; Sari, Lusi Rahma (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2025)
Orthodontic treatment is one way to deal with malocclusion problems to achieve good dental occlusion. As a result of the phenomenon of individual needs in overcoming malocclusion, many people come to the dentist's practice to install braces at different rates. This study aims to determine the most dominant factor in influencing the rates of braces fitting in general dental practices in Medan. This type of research is descriptive analytic with cross sectional approach. The study population was dentists who practised actively in Medan and performed fixed orthodontic treatment or braces. The sample size was 30 people with purposive sampling. Data were collected through questionnaires. Data analysis used Spearman's Correlation test and multiple linear regression. The results showed that the mean of the type of braces, practice location, and type of malocclusion were 3.17 ± 0.950; 3.77 ± 0.504; and 9.13 ± 1.383, while the rate of braces had a mean of 1.37 ± 0.490. Spearman;s correlation statistical test can be stated that there is an influence of the type of brace (p=0.002; p≤0.05), practice location (p=0.039; p≤0.05), and type of malocclusion (p=0.005; p≤0.05) on the determination of significant dental practice brace tariffs in Medan Petisah District. The type of brace had a strong degree of influence, while the location of the practice and the type of malocclusion showed a moderate degree of influence. The type of brace is the most dominant factor in influencing the determination of tariffs. The conclusion of this study is that the better the type of brace, the more expensive the fitting rate.